Does Long-Term Selection for Development Time Result in Canalization: A Test Using Drosophila melanogaster - Ghosh, Shampa M.; Satish, K. M.; Jayaram, Mohan; Joshi, Amitabh (Frontiers in Ecology and Evolution, 2019)
Canalization denotes the robustness of a trait against genetic or environmental perturbation. Plasticity, in contrast indicates the environmental sensitivity of a trait. Stabilizing selection is thought to increase canalization of a trait, whereas directional selection is often thought to lead to decanalization. However, the relationship between selection, canalization and plasticity remains largely unclear. Experimental evolution is a powerful approach for addressing fundamental questions in evolution. Here, we ask whether long-term directional selection for reduced development time in Drosophila melanogaster results in the evolution of increased canalization for development time, the trait under primary selection. We additionally investigate whether pre-adult survivorship, a trait only secondarily under selection in this experimental regime, also evolves to become canalized. We examine canalization both in terms of stability of population means and of within population variability across two environmental axes, reflecting macro- and microenvironmental canalization. We used four large outbred populations of D. melanogaster selected for rapid pre-adult development and early reproduction for 295 generations, and four corresponding ancestral control populations that were not under conscious selection for development time or early reproduction. The selected populations had evolved 25% reduction in both development time and pre-adult survivorship at the time of this study. We studied development time and pre-adult survivorship of the selected populations and controls across various combinations of rearing temperature and larval density. Development time in the selected populations had become more canalized, both macro- and microenvironmentally, than controls with regard to density, but not temperature. Canalization of development time across density appears to have evolved due to evolutionary changes in the life-history and physiology of the selected populations. Pre-adult survivorship, only a secondary correlate of fitness in the selected populations, did not show any clear trend in terms of canalization with regard to either density or temperature, and, overall variation in the trait was greater compared to development time within and across environments. Whether long-term directional selection canalizes or not, therefore, appears to be dependent in a complex way on specific interactions of trait, selection regime and environmental factor in the context of the ecology and physiology of the popualtions under study.